Pengaruh Latihan Cirquit Circle Passing Drill Terhadap Peningkatan Keterampilan Passing Pemain Academy U10-U12 - Achmad Dwi Setio; Nurman Ramadhan; Rohmat Apriyanto (Jurnal Porkes, 2026)
This study aims to analyze the effect of circuit circle passing drills on improving inner foot passing skills in U10–U12 youth academy players. The main problem in coaching basic techniques at an early age is low accuracy, consistency, and situational understanding when passing. This study uses a quantitative approach with a one-group pretest-posttest pre-experimental design. The research population consists of all U10–U12 young star academy players, and the sample consists of 15 players selected through total sampling. Data collection instruments included a passing accuracy test (score range 0-10) and a technique observation sheet with five assessment indicators. Data analysis was performed using the Shapiro-Wilk normality test and the paired sample t-test to determine the difference in ability before and after treatment. The core training consisted of a circuit circle passing drill at three stations, followed by a cool-down. The results showed a significant improvement in passing ability, marked by an increase in the average score from 8.07 (pretest) to 11.67 (posttest) with a significance value of < 0.001. The conclusion of this study confirms that the circuit circle passing drill method is effective in improving the inside foot passing skills of young players, so it can be recommended as an alternative training model in basic soccer technique coaching.